DOI: 10.11606/d.82.2010.tde-20072012-090651
|View full text |Cite
|
Sign up to set email alerts
|

Preparo e caracterização físico-química e biológica de um biocompósito à base de celulose associada à própolis

Abstract: Em primeiro lugar à Deus que foi meu grande apoio durante toda a minha vida em todos os momentos. Aos meus pais Olga e José Emilio e aos meus irmãos Carla e Mateus que sempre estiveram ao meu lado dando-me apoio, carinho e força para conseguir vencer as dificuldades e saudades, agradeço à Deus todos os dias por vocês existirem. Em especial minha esposa Bianca e minha filhinha Maria Clara que sempre me apoiaram no que foi preciso para a minha formação e na minha profissão, estando sempre ao meu lado, me proporc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…The adsorption of the extract on the membrane has created a kind of film on its surface, filling the pores and covering the BC nanofibers. This behavior was also observed by PICCHI [33] in his studies involving the incorporation of propolis into the BC membrane.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 74%
See 1 more Smart Citation
“…The adsorption of the extract on the membrane has created a kind of film on its surface, filling the pores and covering the BC nanofibers. This behavior was also observed by PICCHI [33] in his studies involving the incorporation of propolis into the BC membrane.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 74%
“…Furthermore, the bands close to 3300 cm -1 , 2900 cm -1 and 1000 cm -1 showed greater intensity with the addition of the aqueous extract. According to PICCHI [33] the band's broadening at 3300 cm -1 , referring to the C-OH bond, may be related to forming a hydrogen bond between witch hazel and cellulose.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…The determination of the maximum concentrations of each component was performed from preliminary tests, where the formation of flexible, easy-to-handle, and homogeneous structures (films) was evaluated. In addition, the values were based on works published in the literature, such as the study by Picchi [56], which demonstrated that BC membranes with at least 2.0 g of dry mass of propolis presented a satisfactory antimicrobial activity for application as a wound dressing. The values of the standards were established according to the study of Machado et al [57] for the green propolis sample, where the value found for p-coumaric acid was approximately 8.0 mg, the same value found for biochanin A in the red propolis samples.…”
Section: Preparation Of the Wound Dressingsmentioning
confidence: 99%